An Analysis of Code Mixing Used by A Singaporean Singer in Instagram’s Caption - Tira Nur Fitria (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
This study aims to find out the type of code-mixing and the most dominant type of code-mixing used by Rosalina Musa in Instagram’s caption. This research is descriptive qualitative as the method of the research. From the result of the analysis shows an outer code mixing found in Rosalina Musa’s Instagram captions. It blends or mixes a native language with a foreign language. From the definitions stated, there are some types of code-mixing found in Rosalina Musa’s Instagram captions, they are the example is the English language is mixed with the Indonesian language. The forms of code-mixing usually appear in word, phrase, clause, hybrid, and repetition/reduplication. In a word, there are 152 data or 53.33 %. In a phrase, there are 113 data or 39.65 %. In the clause, there are 12 data or 4.21 %. In a hybrid, there are 6 data or 2.11 %. While in repetition/reduplication there are 2 data or 0.70 %. It also shows that the most dominant type of code-mixing found in Rosalina Musa’s Instagram captions appears in the word. The insertion of words here means the language unit that stands on its own, it consists of free morpheme sand bound morphemes. The words include some part of speech or word class, for example, noun, adjective, verb, conjunction, and adverb.